2005
DOI: 10.1002/art.20939
|View full text |Cite
|
Sign up to set email alerts
|

A novel ultrasonographic synovitis scoring system suitable for analyzing finger joint inflammation in rheumatoid arthritis

Abstract: Objective. To develop an ultrasonographic (US) synovitis scoring system suitable for evaluation of finger joint inflammation in patients with active rheumatoid arthritis (RA) and to compare semiquantitative US scoring with quantitative US measurements.Methods. US was performed at the palmar and dorsal sides of the second through fifth metacarpophalangeal (MCP) and proximal interphalangeal (PIP) joints in 10 healthy subjects and in the clinically more affected hand in 46 RA patients. Ten patients additionally u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
193
1
28

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(227 citation statements)
references
References 37 publications
5
193
1
28
Order By: Relevance
“…The US scanning method has been described previously (5,10,14,16,33,34). Synovitis, tenosynovitis, and bursitis were defined according to the Outcome Measures in Rheumatology Clinical Trials published definitions and descriptions (14,16,35,36).…”
Section: Methodsmentioning
confidence: 99%
“…The US scanning method has been described previously (5,10,14,16,33,34). Synovitis, tenosynovitis, and bursitis were defined according to the Outcome Measures in Rheumatology Clinical Trials published definitions and descriptions (14,16,35,36).…”
Section: Methodsmentioning
confidence: 99%
“…Of 3004 studies identified initially, 14 articles were selected to be included in the review 8,9,14,25,26,27,28,29,30,31,32,33,34,35 . Table 1 shows the study design characteristics of the studies.…”
Section: Journal Of Rheumatologymentioning
confidence: 99%
“…The on October 31, 2016 -Published by www.jrheum.org Downloaded from based on suggested frequency of involvement 25 , feasibility 8 , or representative value of target joints 9 , or were developed in a logistic regression model 26 . Two reduced joint counts seemed to present good validity issues: the 12-joint count proposed by Naredo, et al 26 and the 7-joint count by Backhaus, et al 25 .…”
Section: Journal Of Rheumatologymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to quantify the pathologic changes in single joints, synovitis may be evaluated by binary grading (presence/absence), semiquantitative scoring (scales), and quantitative measurements (volume/depth of synovial tissue), both in gray-scale (GS) (8,(13)(14)(15) and also by using color/power Doppler (PD) flow assessment (16 -23). In recent years, several global ultrasound synovitis scoring systems that aim to assess synovitis on the patient level as opposed to the level of single joints have been developed and validated (24).…”
Section: Introductionmentioning
confidence: 99%